Analisis Campur Kode pada Acara Podcast di Youtube Chanel Sule Production Ini Bukan Talkshow - Risman Nama Sabon; Suyatno Suyatno (Journal of Social, Culture, and Language, 2023)
This research aims to describe the form of code mixing and the form of code mixing in the Podcast Event on Youtube Chanel Sule Production, this is not a talkshow. The type of research used in this research is descriptive. Collecting data using the method of free involvement and expert observation. Data analysis was carried out using qualitative methods. The object of this study is the Podcest Show on Yotube Chanel Sule Prodaction This is not a Talkshow. The results of the study identified 37 data which were divided into 12 code-mixing forms and 25 outward code-mixing forms. As well as the form of code mixing found in the form ofa. Inserting word elements, 15 data inserting word elements, 10 data inserting phrase elements, 5 data baster form inserts, and 1 clause inserting data elements. Keywords:Sule Prodaction, Youtube, Code mixing